Pengaruh Kesadaran Merek, Kesan Kualitas Dan Asosiasi Merek Terhadap Keyakinan Pelanggan Dalam Membeli Pasta Gigi Merek Pepsodent (Studi Di Desa Sumberagung Bojonegoro) - Wiwit Devi Kurnia, ; Widyastuti, (Bisnis dan Manajemen, 2011)
At the current market conditions, consumers are faced with an increasingly diverse product choices, brand identity will make the product selection process easier, because it helps consumers to decide which products best suited to their needs. Brand is a symbol and an indicator of quality of a product. Product brands that have long been known by consumers have become a status symbol and even the image for the product. So it is not surprising if the brand is often used as criteria in evaluating a product. (Sumarwan, 2002:303). The type of this research is a conclusive study uses causal research. The population of this study were men and women at least 19 years of age. The sample in this study are the customers of Pepsodent toothpaste in Sumberagung villages, Bojonegoro as many as 110 respondents. Non probability sampling technique using Purposive sampling way is used to determine the sample of this research. The data of this research analized by multiple linier regression analysis. The result of this research shows coefficient of determination 0,628, it means that there is an influence variable independent to dependent variable equal to 62,8% and the rest of 37,2% influenced by other variables outside this research. The most dominant variable in this research is brand awareness variable by t value of 6,109.